Nurr1 (NR4A2) regulates Alzheimer's disease‐related pathogenesis and cognitive function in the 5XFAD mouse model. Issue 1 (4th December 2018) - Moon, Minho; Jung, Eun Sun; Jeon, Seong Gak; Cha, Moon‐Yong; Jang, Yongwoo; Kim, Woori; Lopes, Claudia; Mook‐Jung, Inhee; Kim, Kwang‐Soo
Abstract: The orphan nuclear receptor Nurr1 (also known as NR4A2 ) is critical for the development and maintenance of midbrain dopaminergic neurons, and is associated with Parkinson's disease. However, an association between Nurr1 and Alzheimer's disease (AD)‐related pathology has not previously been reported. Here, we provide evidence that Nurr1 is expressed in a neuron‐specific manner in AD‐related brain regions; specifically, it is selectively expressed in glutamatergic neurons in the subiculum and the cortex of both normal and AD brains. Based on Nurr1's expression patterns, we investigated potential functional roles of Nurr1 in AD pathology. Nurr1 expression was examined in the hippocampus and cortex of AD mouse model and postmortem human AD subjects. In addition, we performed both gain‐of‐function and loss‐of‐function studies of Nurr1 and its pharmacological activation in 5XFAD mice. We found that knockdown of Nurr1 significantly aggravated AD pathology while its overexpression alleviated it, including effects on Aβ accumulation, neuroinflammation, and neurodegeneration. Importantly, 5XFAD mice treated with amodiaquine, a highly selective synthetic Nurr1 agonist, showed robust reduction in typical AD features including deposition of Aβ plaques, neuronal loss, microgliosis, and impairment of adult hippocampal neurogenesis, leading to significant improvement of cognitive impairment. These in vivo and in vitro findings suggest that Nurr1 critically regulates AD‐related pathophysiology and identify Nurr1 as a novel AD therapeutic target.